Alignment of standards through semantic tools-The case of land administration - Stubkjaer, Erik; Cagdas, Volkan (ELSEVIER SCI LTD, 2021)
The fact that both the ISO 19152:2012 Land Administration Domain Model (LADM) and the OGC 15?111r1 Land and Infrastructure Conceptual Model Standard (LandInfra) exist within the domain of Land Administration, calls for a mediating platform, which could support an alignment of the standards. The purpose of this article is to demonstrate, how semantic tools have been used to establish such platform. Semantic tools include thesauri. The Cadastre and Land Administration Thesaurus (CaLAThe) was issued in 2011 and based on the then draft version of the ISO LADM standard. CaLAThe was further developed to include also terms of the OGC LandInfra standard of 2016. The recent version (December 2019) integrates code list names and values, reflecting both the relevant Survey and Land division parts of LandInfra and, as proof of concept, some of the code lists mentioned in the Annex J Code lists of LADM. CaLAThe thus constitutes a shared universe of discourse, a frame for joint management of the code lists of the mentioned standards. Taking a problem-based approach to the design of artefacts like standards, the mentioned alignment of standards is part of a problem hierarchy. In this hierarchy, development of information standards provides a means for improving public administration, more specifically its aspects of e-government and interoperability. These aspects have spurred interest in semantic tools; for example, standardization organizations have recently publicized their terminological resources in terms of the ISO/TC211 Geolexica glossary and the OGC Definitions Server. The definitions of CaLAThe and the mentioned code lists are by December 2019 included into the OGC Definitions Server. Besides servicing the Land Administration communities, CaLAThe illustrates the use of thesauri as a cross-domain means for supporting the alignment of standards.
Keywords: ISO LADM; OGC LandInfra; InfraGML; Alignment of standards; E-government; Interoperability; Knowledge Organization Systems (KOS); Cadastre and Land Administration Thesaurus& nbsp; (CaLAThe); ONTOLOGY; VOCABULARY; Environmental Sciences & Ecology